2014
DOI: 10.1242/jeb.101600
|View full text |Cite
|
Sign up to set email alerts
|

Water surface locomotion in tropical canopy ants

Abstract: Upon falling onto the water surface, most terrestrial arthropods helplessly struggle and are quickly eaten by aquatic predators. Exceptions to this outcome mostly occur among riparian taxa that escape by walking or swimming at the water surface. Here we document sustained, directional, neustonic locomotion (i.e. surface swimming) in tropical arboreal ants. We dropped 35 species of ants into natural and artificial aquatic settings in Peru and Panama to assess their swimming ability. Ten species showed directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Interface 12: 20150534 eyes [15], and appear to use visual cues to locate tree trunks during a fall, as do gliding ants [4]. For gliding ants, experimental placement in either the understory or in local waters substantially increases mortality at the figurative hands of either arthropod predators or fish, respectively [2,3]. The behavioural consistency of directed aerial descent, both within and among those arthropod lineages studied to date, suggests substantial advantages to remaining within the canopy once airborne.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interface 12: 20150534 eyes [15], and appear to use visual cues to locate tree trunks during a fall, as do gliding ants [4]. For gliding ants, experimental placement in either the understory or in local waters substantially increases mortality at the figurative hands of either arthropod predators or fish, respectively [2,3]. The behavioural consistency of directed aerial descent, both within and among those arthropod lineages studied to date, suggests substantial advantages to remaining within the canopy once airborne.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, wingless arthropods dwelling within tree crowns face significant hazards if they fall to the forest floor. Landing within the understory presents both unfamiliar terrain and a suite of ground-dwelling predators which, in some cases, may rapidly and lethally attack such intruders from the canopy [2,3]. To avoid these problems, workers of many ant species, and many other wingless hexapods, orient their falls towards tree trunks upon which they land [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although adults are unpalatable, it has been suggested that their eggs may be subject to predation or removed from leaves by Ectatomma ants, which are often found on Solanum species [35]. As Ectatomma ants are weak swimmers [36] and do not normally occur in Amazonian seasonally-flooded forests [37], we hypothesize that their absence may favor the high abundance of Oleria in vaó rzea forests.…”
Section: Discussionmentioning
confidence: 97%
“…A repeating pattern (instead of a single stripe) was used in order to ensure that ants traversing the tube would perhaps perceive a stronger signal before reaching the forking point. Black stripes have been used in orientation studies on other animals, such as moths (Preiss and Kramer, 1984) and ants (Handlon, 2015;Yanoviak and Frederick, 2014 In for right turns Fig. 2.…”
Section: Y-mazementioning
confidence: 99%